Kepatuhan terhadap Rezim Anti Pencucian Uang Internasional melalui Rekomendasi FATF: Perbandingan Dua Negara - Zakiah, Alif Ilma (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2024)
Indonesia became a dual member of the Asia/Pacific Group (APG) and Financial Action Task Force (FATF) in October 2023, having previously been grey listed twice in the past 20 years. Meanwhile, Vietnam was added to the Jurisdiction Under Increased Monitoring list in June 2023, despite being an APG member since 2007. This study compares the AML/CFT/CPF risks, threats, and compliance between these two Southeast Asian developing economies using six indicators: Human Development Index (HDI), Corruption Perception Index (CPI), Gross Domestic Products (GDP), Anti Money Laundering (AML) regulations, National Risk Assessment (NRA), and Mutual Evaluation Report (MER). Findings show Vietnam’s HDI ranking surpasses Indonesia’s, but Vietnam lags in GDP and AML regulations. Both countries share similar AML risks, threats, and CPI scores. However, Indonesia’s approach prioritizes national interests over international ones, contributing to its FATF compliance success. This comparative analysis offers valuable insights for Vietnam and other grey-listed Association of Southeast Asian Nations (ASEAN) countries seeking to enhance compliance with FATF Recommendations.